InunIB: Analysis of a flood database for the Balearic Islands - Joan ROSSELLO; Miquel GRIMALT (European Journal of Geography)
This paper presents a database that includes all the known flood events in the Balearic Islands from the 15th century to 2018. The research uses historical sources, such as chronicles, church records and public archives, while for recent events, the data is obtained from newspapers information and official reports from local and regional authorities. The result is that more than 200 floods have been identified. The next step is study the obtained data. In that sense, the temporal distribution is analysed. Some other characteristics, such as the evolution of damaged areas or the increase of events during the 20th century, are presented. The database structure allows to be updated after recent events and the data presented can be considered as a first step to gain a valuable knowledge of the flooding risk in the Balearic Islands and can contribute to provide information on future events in terms of spatial and temporal flood impact